The developing human : clinically oriented embryology - Moore, Keith L.; Persaud, T. V. N.; Torchia, Mark G. (Edinburgh : Elsevier, 2020)
Covers normal and abnormal embryonic and fetal development, linking basic science with clinical practice for medical and health science students.
Includes bibliographical references and index.
Keywords: Embryology; Human development; Congenital abnormalities